The antibacterial activity of Trigonella foenum-graceum extracts against bacteria that causes Otitis media in children. - Zaid Khalaf Abdullah (College of Pharmacy / Mustansiriyah University, 2013)
Two hundred fifty ear swab samples were collected from patient with Otitis media in children between 6-12 years old in the central children hospital in Baghdad for a period between July 2011 to December 2011. The diagnosis of the isolates showed that 150 samples were positive to isolate bacterial culture indicate the presence of Proteus spp. 48(32%) then Staphylococcus spp. 45(30%), Pseudomonas spp. 40(26.6%) then Escherichia coli 17 (11.3%). The susceptibility of the isolates to antimicrobial agents were tested on seven antimicrobial agents by using disc diffusion assay. The antimicrobial agents were ampicilin, Gentamycin, cephalothin, rifampin, tetracyclin, streptomycin, amikaci. All the isolates resist the streptomycin, tetracycline, rifampin,cephalothin and ampicillin. The alcoholic and water extract of Trigonela foenum graceum shows activity against the four bacterial genuses. The (MIC) values for alcohol extract were (25mg/ml for Staphylococcus spp, 12.5mg/ml for E. coli, (25mg/ml) for Proteus spp. and 12.5 mg/ml for pseudomonas spp. The (MIC) values for the water extract were (25mg/ml) for Staphylococcus spp.,(12.5mg/ml )for E.coli and (25mg/ml) for both Proteus spp. and Pseudomonas spp.